O direito fundamental ao desenvolvimento e a inconstitucionalidade do emprego da taxa de juros como instrumento central da política estatal brasileira - Ervedosa, Nathalia Damasceno da Costa e Silva (2011)
This essay aims to analyze the treatment given to Brazilian constitution to the right to development, relating it to the use of interest rate as an instrument of national public center policy; focusing on the role that interest rate plays in channeling the flow of money, influencing decisively the credit (claim) and, therefore, the productive activity of the state. Thus, we approach the interest rate under the micro and macro juridical view, we study the plan and its importance in the consolidation of economic policy, and we see the need of coordination between the monetary, the exchange rate and fiscal budget policies to perform the economic policy objectives. We conclude that in Brazil, since there is not observed the existence of economic policy given to the failure of economic planning implemented by Brazilian State, the state intervention in the economic domain occurs merely conjecturaly and in random. We noticed that, refraining from resorting from other instruments of economic policy outlined by our legal framework, the economic policy is reduced to monetary policy, which main objective confines itself to the maintenance of monetary stability. Thus, the state public policy remains limited to the manipulation of the basic interest rate as a mechanism to control inflation and to finance the state budget deficit, ignoring the adverse effects of maintaining the high interest rates on the productive sector. It is evident, therefore, the unconstitutionality of the brazilian state public policy as it is currently conducted, once it behold the country to his duty to promote the fundamental right to development.